Scrotal Apocrine Adenocarcinoma with Pagetoid Phenomenon and Inguinal Lymph Node Metastases - Aristeidis Hristos Zibis; Apostolos Haralampos Fyllos; Sophia Havaki; Sotirios Sotiriou; Georgios Kotakidis; Dimitrios Leonidas Arvanitis (Case Reports in Oncological Medicine)
We report a case of scrotal apocrine adenocarcinoma in a 72-year-old Caucasian male which was initially presented as a reddish superficial lesion which in time became an ulcerated nodule. The initial pathological examination showed an apocrine adenocarcinoma with pagetoid phenomenon. The tumor recurred after four months and then excision biopsy showed tumor with pagetoid phenomenon which reached all the surgical margins. Three months later an ulcerated nodule in the scrotum and greatly enlarged ipsilateral inguinal lymph nodes were noticed. The final pathological examination showed multiple separated malignant foci, some with overlying pagetoid phenomenon and inguinal lymph node metastases. Immunohistochemistry showed positivity for Gross Cystic Disease Fluid Protein-15 (GCDFP-15), androgen receptors, and score 3+ for the Human Epidermal growth factor Receptor-2 (HER2). The aggressive behavior of the present tumor goes along with previous reports showing that HER2 high score cases exhibit a worse prognosis.